Development of Multimedia-Based Basketball Arbitration Learning Media - Nuranti, Dina Ami; Rahayu, Tandiyo; Kasmini Handayani, Oktia Woro (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2018)
This development research aims to produce multimedia-based multimedia learning products that are valid and effective against the improvement of material understanding on the students of Basketball Coaching of Sports Education Department of Semarang State University. Research development is done through the steps: potentials and problems, data collection, product design, design validation, design revisions, product trials, product revisions, usage trials, product revisions, and mass production. The developed learning media contains basketball arbitration material that is a violation and foul signals, violation moves, fouls practiced by visuals, as well as games equipped with videos and quizzes. The result of the assessment effective learning media to increase students' understanding. In small groups, there was an increase from 75.26 to 84.74 with tvalue = 4.869 and significance of 0.000 < 0.05. After the media revision and tested in large groups, material understanding increased from 75.33 to 89.33 with tvalue = 6.548 and significance of 0.000 < 0.05. It was concluded that multimedia-based learning media developed pertained valid and effective as well as learning media can be accessed by using the laptop by installing adobe flash first and smartphone because this media already equipped with APK application so that direct can be used a smartphone by installing it.